Knitlandia : a knitter sees the world - Parkes, Clara (STC Craft, 2016)
"Knitting aficionado and notable artisan Clara Parkes delves into her storied travels with this inspiring and witty memoir on a creative life enriched by her adventures around the world. Building on the success of The Yarn Whisperer, Parkes's rich personal essays invite readers and devoted crafters on excursions to be savored, from a guide who quickly comes to feel like a trusted confidante. In Knitlandia, she takes readers along on 17 of her most memorable journeys across the globe over the last 15 years, with stories spanning from the fjords of Iceland to a cozy yarn shop in Paris's 13th arrondissement. Also known for her PBS television appearances and hugely popular line of small-batch handcrafted yarns, Parkes weaves her personal blend of wisdom and humor into this eloquently down-to-earth guide that is part personal travel narrative and part cultural history, touching the heart of what it means to live creatively."--Provided by Amazon.com.